Oxford Scholarship Online 2018
DOI: 10.1093/oso/9780198786627.003.0015
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the Convention on the Rights of Persons with Disabilities in Domestic Courts

Abstract: This chapter reflects on the ways in which courts in the thirteen jurisdictions included in this study have interpreted the provisions of the Convention on the Rights of Persons with Disabilities (CRPD). Firstly, it explores the interpretations which CRPD provisions (from the Preamble to Article 30) have been given by different courts in cases analysed in this study. Secondly, it considers various issues concerning the interpretations of the CRPD adopted in the thirteen jurisdictions. This discussion begins by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The status of the CRPD in the domestic courts of dualist states is persuasive where domestic law is ambiguous or unsettledit is not binding in law. Yet a recent comparative study of 13 jurisdictions found that the domestic courts of both monist and dualist states are increasingly considering and interpreting the CRPD in order to fill gaps in domestic law, and to update it, even if not always quite in line with the intentions of its drafters (Lawson and Waddington 2018).…”
Section: Legal Status and Influencementioning
confidence: 99%
See 1 more Smart Citation
“…The status of the CRPD in the domestic courts of dualist states is persuasive where domestic law is ambiguous or unsettledit is not binding in law. Yet a recent comparative study of 13 jurisdictions found that the domestic courts of both monist and dualist states are increasingly considering and interpreting the CRPD in order to fill gaps in domestic law, and to update it, even if not always quite in line with the intentions of its drafters (Lawson and Waddington 2018).…”
Section: Legal Status and Influencementioning
confidence: 99%
“…The CRPD's broad description of the target population is already reshaping states parties' approach to disability (Kakoullis and Ikehara in Bantekas et al 2018;Lawson and Waddington 2018). For example, in 2013 the Court of Justice of the European Union adopted the CRPD's approach to disability, reversing an earlier medical model definition relied upon by the EU (HK Danmark v. Dansk almennyttigt Boligselskab, 2013).…”
Section: A Human Rights Model Of Disability?mentioning
confidence: 99%